Arsenic Bioaccessibility of Realgar Influenced by the Other Traditional Chinese Medicines in Niuhuang Jiedu Tablet and the Roles of Gut Microbiota. (18th December 2019) - Xu, Wenfeng; Xu, Shuo; Zhang, Shanshan; Wu, Xuejun; Jin, Pengfei
Abstract : Niuhuang Jiedu tablet (NJT), a realgar (As2 S2 ) containing Traditional Chinese Medicine (TCM), is a well-known formula. The safety of NJT is of growing concern since arsenic (As) is considered as one of the most toxic elements. NJT was demonstrated to be safer than realgar by our previous experiments and some other studies. The toxicity of realgar has been shown to be related to the amount of soluble or bioaccessible arsenic. In this study, the influences of the other TCMs in NJT on the bioaccessibility of arsenic from realgar, and the roles of gut microbiota during this process were investigated in vitro . Results showed that Dahuang ( Rhei Radix et Rhizoma ), Huangqin ( Scutellariae Radix ), Jiegeng ( Platycodonis Radix ), and Gancao ( Glycyrrhizae Radix et Rhizoma ) could significantly reduce the bioaccessibility of arsenic from realgar in artificial gastrointestinal fluids. Gut microbiota played an important role in decreasing the bioaccessibility of realgar because it was demonstrated to be able to absorb the soluble arsenic from realgar in the incubation medium. Dahuang, Huangqin, and Jiegeng could modulate the gut microbiota to enhance its arsenic absorption activity.